Constructing the Epistemology of Islamic Education: Lecturers’ Perspectives from IAI Nusantara Asshiddiqiyah Lempuing OKI - Ahmad Rojali; Saipul Annur; Ermis Suryana; Leni Marlina (At Turots: Jurnal Pendidikan Islam, 2026)
This research is motivated by the importance of understanding the epistemological construction of Islamic education within Islamic universities, particularly how lecturers interpret sources, assess validity, and orient their academic practice. This research aims to analyze the epistemological construction of Islamic education from lecturers’ perspectives and to identify its implications for the development of Islamic learning and science. The research uses a qualitative approach within an empirical study. Data were collected through in-depth interviews, observations, and documentation, and then analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the epistemological construction of Islamic education, as understood by lecturers, relies on the integration of revelation, reason, experience, and social reality as the basis for knowledge development. This perspective is reflected in the lecturer’s views on the relationship between religious science and general science, the purpose of Islamic education, and learning strategies that emphasize the balance of normative, rational, and contextual aspects. This research enriches the study of epistemology in Islamic education through empirical data and offers implications for strengthening scientific paradigms, curriculum design, and learning practices in Islamic universities.